Comprehensive analysis on phenotype and genetic basis of Chinese Fanconi anemia patients: dismal outcomes call for nationwide studies - Daijing Nie; Jing Zhang; Fang Wang; Wei Zhang; Lili Liu; Xue Chen; Yang Zhang; Panxiang Cao; Min Xiong; Tong Wang; Ping Wu; Xiaoli Ma; et al. (BMC, 2020)
Abstract Background Fanconi anemia (FA) is the most common inherited bone marrow failure (BMF) syndrome with 22 related genes identified. The ALDH2 rs671variant has been proved related to accelerate the progression of BMF in FA patients. The phenotype and genetic basis of Chinese FA patients have not been investigated yet. Methods We analyzed the 22 FA-related genes of 63 BMF patients suspected to be FA. Clinical manifestations, morphological and cytogenetic feathers, ALDH2 genotypes, treatment, and outcomes of the definite cases were retrospectively studied. Results A total of 21 patients were confirmed the diagnosis of FA with the median age of BMF onset was 4-year-old. The number of patients manifested as congenital malformations and growth retardation were 20/21 and 14/21, respectively. BM dysplasia and cytogenetic abnormalities were found in 13/20 and 8/19 patients. All the patients with abnormal karyotypes also manifested as BM dysplasia or had evident blasts. Thirty-five different mutations were identified involving six genes and including twenty novel mutations. FANCA mutations contributed to 66.67% of cases. Eight patients harboring ALDH2-G/A genotype have a significantly younger age of BMF onset (p = 0.025). Within the 19 patients adhering to continuous follow-up, 15 patients underwent hematopoietic stem cell transplantations (HSCTs). During the 29 months of follow-up, 8/19 patients died, seven of which were HSCT-related, and one patient who did not receive HSCT died from severe infection. Conclusions The phenotypic and genetic spectrum of Chinese FA patients is broad. Bone marrow dysplasia and cytogenetic abnormalities are prevalent and highly consistent. The overall outcome of HSCTs is disappointing. Nationwide multicenter studies are needed for the rarity and adverse outcome of this disease.